Laser effects based optimal laser parameter identifications for paint removal from metal substrate at 1064 nm: a multi-pulse model. Issue 19 (28th October 2017) - Han, Jinghua; Cui, Xudong; Wang, Sha; Feng, Guoying; Deng, Guoliang; Hu, Ruifeng
Abstract: Paint removal by laser ablation is favoured among cleaning techniques due to its high efficiency. How to predict the optimal laser parameters without producing damage to substrate still remains challenging for accurate paint stripping. On the basis of ablation morphologies and combining experiments with numerical modelling, the underlying mechanisms and the optimal conditions for paint removal by laser ablation are thoroughly investigated. Our studies suggest that laser paint removal is dominated by the laser vaporization effect, thermal stress effect and laser plasma effect, in which thermal stress effect is the most favoured while laser plasma effect should be avoided during removal operations. Based on the thermodynamic equations, we numerically evaluated the spatial distribution of the temperature as well as thermal stress in the paint and substrate under the irradiation of laser pulse at 1064 nm. The obtained curves of the paint thickness vs. threshold fluences can provide the reference standard of laser parameter selection in view of the paint layer with different thickness. A multi-pulse model is proposed and validated under a constant laser fluence to perfectly remove a thicker paint layer. The investigations and the methods proposed here might give hints to the efficient operations on the paint removal and lowering the risk of substrate damages.